2015
DOI: 10.1016/j.progsolidstchem.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in perovskites: Processing and properties

Abstract: The perovskite structure is one of the most wonderful to exist in nature. It obeys to a quite simple chemical formula, ABX 3 , in which A and B are metallic cations and X, an anion, usually oxygen. The anion packing is rather compact and leaves interstices for large A and small B cations. The A cation can be mono, di or trivalent, whereas B can be a di, tri, tetra, penta or hexavalent cation. This gives an extraordinary possibility of different combinations and partial or total substitutions, resulting in an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(77 citation statements)
references
References 173 publications
0
63
0
3
Order By: Relevance
“…It has been concluded that atmosphere itself does not matter in irradiation effects on α; the important factor is whether sufficient energy is provided or not by light and/or heat. They were characterized by elemental analysis (Table 2), high resolution solid-state 13 C NMR (powder) (Figure 8), 100 IR absorption (KBr) spectra, 104,105 UVvis diffuse reflectance spectra (KBr), 104,105 MALDI-TOF MS (Figure 9), 100 N 1s and Ag 3d XPS (Figure 10), 103 Ag MNN Auger spectra (Figure 11), Ag L 3 X-ray absorption near edge structure (XANES) (Figure 12), 99,101 Ag extended X-ray absorption fine structure (EXAFS) (Figure 13), 101 electrical resistivity (Figure 14), magnetic susceptibility (Figure 15), 80,81,105 and X-ray diffraction (XRD) powder patterns ( Figure 16). The Ag + ions are generally known to respond to UV, but their actual photochemistry sensitively depends on coexistent chemical species.…”
Section: Development Of New Types Of Equipmentmentioning
confidence: 99%
“…It has been concluded that atmosphere itself does not matter in irradiation effects on α; the important factor is whether sufficient energy is provided or not by light and/or heat. They were characterized by elemental analysis (Table 2), high resolution solid-state 13 C NMR (powder) (Figure 8), 100 IR absorption (KBr) spectra, 104,105 UVvis diffuse reflectance spectra (KBr), 104,105 MALDI-TOF MS (Figure 9), 100 N 1s and Ag 3d XPS (Figure 10), 103 Ag MNN Auger spectra (Figure 11), Ag L 3 X-ray absorption near edge structure (XANES) (Figure 12), 99,101 Ag extended X-ray absorption fine structure (EXAFS) (Figure 13), 101 electrical resistivity (Figure 14), magnetic susceptibility (Figure 15), 80,81,105 and X-ray diffraction (XRD) powder patterns ( Figure 16). The Ag + ions are generally known to respond to UV, but their actual photochemistry sensitively depends on coexistent chemical species.…”
Section: Development Of New Types Of Equipmentmentioning
confidence: 99%
“…Piezoelectricity was discovered by Pierre and Jacques Curie in 1880 while studying the effect of pressure on the generation of electrical charges by some natural crystals . Piezoelectric materials can undergo a phase transition where the centrosymmetric cubic structure transfers to the first low‐symmetry structure exhibiting a spontaneous polarization, occurring at a certain temperature which is defined as the Curie temperature ( T c ) . A characteristic example of a structure which exhibits a spontaneous polarization with a certain Curie temperature is the perovskite‐type structure of ABX 3 .…”
Section: Organometal Trihalide Perovskite: Structure and Propertiesmentioning
confidence: 99%
“…The physical and chemical properties and the catalytic activities of these perovskites are greatly affected by the nature, oxidation states and the stochiometry of the elements of A and B . Their compositions, with different combinations of charged cations in the A and B sites (A cation can be mono, di or trivalent, whereas B can be a di, tri, tetra, penta or hexavalent cation) , can be varied over a wide range by partial or total substitutions with a great range of metal cations, the resulting formula is in AA'BB'O3 form (A'andB' are substituted cations) . Conventionally in the literature, Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3‐δ perovskites oxides containing barium (Ba), strontium (Sr), Cobalt (Co) and iron (Fe) are labeled by BSCF symbol.…”
Section: Introductionmentioning
confidence: 97%
“…The perovskite family of materials constitutes an important class of semiconductors [9,10] exhibiting properties suitable for numerous applications, such as electrode materials for solid oxide fuel cells (SOFCs), oxygenpermeating membranes, thermoelectric devices [11], sensors, fuel cells [12] and catalysis in oxidation and reduction processes [13,14]. Recently, oxides with perovskite structure have been extensively studied as catalysts in methanol oxidation reaction in acid and alkaline media, due to [ their variety of properties, such as excellent proton transport property, thermal and chemical stability, mechanical, electrical and catalytic properties [11][12][13][14][15] Generally, the crystallographic structural of perovskite-type oxides with the general formula ABO 3 (A: an alkaline earth or a lanthanide metal and B: a transition metal) is presented by a flexible and corner-connected BO 6 octahedral network where B cations are coordinated by 6 oxygen anions, while A cations are coordinated by 12 oxygen anions [12,16]. The physical and chemical properties and the catalytic activities of these perovskites are greatly affected by the nature, oxidation states and the stochiometry of the elements of A and B [17,18] [20,21].…”
Section: Introductionmentioning
confidence: 99%